1975
DOI: 10.1172/jci108031
|View full text |Cite
|
Sign up to set email alerts
|

Uricosuric agents in uremic sera. Identification of indoxyl sulfata and hippuric acid.

Abstract: A B S T R A C T Serum and urine from chronically uremic patients and normal individuals were subjected to gel filtration on Sephadex-G10. The effects of the eluted fractions on the uptake of urate and para-aminohippurate by isolated cortical tubules of rabbit kidney were investigated. According to the origin of the samples, one to three major groups of fractions inhibiting both urate and para-aminohippurate transport were disclosed. The first eluted group occurred for all the samples under study. The second on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 24 publications
2
28
0
2
Order By: Relevance
“…2; Table 4). HA significantly inhibited PAH transport in the kidney (Boumendil-Podevin et al, 1975), suggesting that both compounds are transported by the organic anion transport system. Recently, we demonstrated that rOat1 and human OAT1 (hOAT1) play an important role in renal uptake of HA (Deguchi et al, 2004).…”
Section: Pharmacokinetics Of Hippurate In Uremia 935mentioning
confidence: 95%
See 1 more Smart Citation
“…2; Table 4). HA significantly inhibited PAH transport in the kidney (Boumendil-Podevin et al, 1975), suggesting that both compounds are transported by the organic anion transport system. Recently, we demonstrated that rOat1 and human OAT1 (hOAT1) play an important role in renal uptake of HA (Deguchi et al, 2004).…”
Section: Pharmacokinetics Of Hippurate In Uremia 935mentioning
confidence: 95%
“…Serum levels of the uremic toxin hippurate (HA) are markedly elevated in patients with uremia ( Vanholder et al, 2003). It has been suggested that HA plays a role in a variety of pathological conditions, including stimulation of ammoniagenesis (Dzurik et al, 2001), and inhibition of both plasma protein binding (Sakai et al, 1995) and organic anion secretion by the kidney (Boumendil-Podevin et al, 1975). HA also inhibits glucose utilization in muscles and so may be involved in development of muscular weakness in uremia (Spustova et al, 1987(Spustova et al, , 1989.…”
mentioning
confidence: 99%
“…17,18 More recently, in vitro studies found that the uremic toxins hippuric acid and indoxyl sulfate effectively inhibited uptake of PAH in isolated rabbit renal tubules and that indoxyl sulfate administered in vivo significantly reduced the renal clearance of PAH in rats. 19,20 These data strongly implicate involvement of the classic organic anion transport system in the renal elimination of uremic 21 Today, this system has been identified as comprising (in part) the OATs within the organic cation/anion/ zwitterion (SLC22) transporter family and it is clear that OATs are key mediators of the transepithelial flux of many endogenous compounds, including acidic uremic toxins. 16,22,23 As such, renally expressed OATs are poised to play a central role in the pathophysiology associated with the intracellular accumulation and toxicity of uremic retention solutes.…”
Section: Oats As Determinants In Tubular Secretion Of Uremic Toxinsmentioning
confidence: 99%
“…However, over time it became more and more clear that the concentration of these solutes can be influenced by many factors. These could be, as also summarized in the review by Stevens and Levey (12), renal tubular secretion (indoxyl sulfate [IS], hippurate) (13), enzymatic metabolism (asymmetric dimethylarginine [ADMA]) (14), intestinal secretion/absorption (uric acid) (15), generation by intestinal flora (indoles, phenols) (16), and/or dietary habits or changes in distribution volume. Therefore, the question can be raised whether GFR predicts elimination and concentration of those solutes and thus their effect on the uremic status in a sufficiently robust manner.…”
Section: Introductionmentioning
confidence: 99%